Certified random number generation using quantum computers - Nath, Pingal Pratyush; Sinha, Aninda; Sinha, Urbasi (Frontiers in Quantum Science and Technology, 2025)
We investigate how current noisy quantum computers can be leveraged for generating secure random numbers certified by Quantum Mechanics. While random numbers can be generated and certified in a device-independent manner through the violation of Bell’s inequality, this method requires significant spatial separation to satisfy the no-signaling condition, making it impractical for implementation on a single quantum computer. Instead, we employ temporal correlations to generate randomness by violating the Leggett-Garg inequality, which relies on the No-Signaling in Time condition to certify randomness, thus overcoming spatial constraints. By applying this protocol to different IBMQ platforms, we demonstrate the feasibility of secure, semi-device-independent random number generation using low-depth circuits with single-qubit gates. We show how error mitigation techniques lead to LGI violation compatible with theoretical predictions on the existing IBMQ machines.